I Will Forgive When Helped: Anger No More - Barima, Solomon Jil; Asamoah-Gyawu, Joseph; Donkoh, Hagar; Inkoom, Daniel; Agyei-Sarppong, Kingsley; Attila, Frank Lamadoku (International Journal of Rehabilitation and Special Education (IJRSE), 2023)
Introduction One of the ways to make a relationship last is to have the ability to forgive offenders, thereby reducing the anger and pain that come with painful actions and words from close friends and associates. According to Abrahamic religions and relationship experts, forgiveness is the path to eternal life and lasting relationships in all spheres of engagement. Methods This quasi-experimental study used pre-test and post-test with experimental and control groups. This study used the Enright Process Model of forgiveness to assess how people can forgive others and reduce anger, using a sample of 26 first-year students from two colleges of education in Ghana. The treatment lasted for six weeks. Instruments the Attitude and General Anger Inventories were used to collect the data. Analysis The data was analysed using Independent Samples t-test and Pearson’s Correlation   Findings The results showed that the model was able to increase the level of forgiveness; however, the level of anger was reduced but it wasn’t significant. There was also an inverse relationship between forgiveness and anger among the respondents. Recommendations Counsellors in Ghana were encouraged to use the model in their work because it shows a promising increase in reducing un-forgiveness. Another suggestion was that other forgiveness models should be tested among college students.
Keywords: Anger; Enright Process Model; Forgiveness,; Offender Relationship.